2023
DOI: 10.3390/cancers15072119
|View full text |Cite
|
Sign up to set email alerts
|

Potential, Limitations and Risks of Cannabis-Derived Products in Cancer Treatment

Abstract: The application of cannabis products in oncology receives interest, especially from patients. Despite the plethora of research data available, the added value in curative or palliative cancer care and the possible risks involved are insufficiently proven and therefore a matter of debate. We aim to give a recommendation on the position of cannabis products in clinical oncology by assessing recent literature. Various types of cannabis products, characteristics, quality and pharmacology are discussed. Standardisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 145 publications
0
2
0
Order By: Relevance
“…The effects of CBD/THC in cancer patients primarily focus on reducing symptom distress, including cancer-related pain, cachexia, nausea, and vomiting. However, conflicting results have been reported in clinical trials, and findings may lack statistical power [ 222 , 223 , 224 , 225 ]. A recent retrospective chart review suggested that there was no statistically significant change in symptom distress with medical cannabis use in cancer patients [ 226 , 227 ].…”
Section: Cbd/thc Studies In Special Populationsmentioning
confidence: 99%
“…The effects of CBD/THC in cancer patients primarily focus on reducing symptom distress, including cancer-related pain, cachexia, nausea, and vomiting. However, conflicting results have been reported in clinical trials, and findings may lack statistical power [ 222 , 223 , 224 , 225 ]. A recent retrospective chart review suggested that there was no statistically significant change in symptom distress with medical cannabis use in cancer patients [ 226 , 227 ].…”
Section: Cbd/thc Studies In Special Populationsmentioning
confidence: 99%
“…There are a lot of studies that describe cannabinoids impact on pain management, Parkinson's disease, spasticity due to multiple sclerosis or paraplegia, epilepsy, ophthalmological diseases, or different kinds of psychiatric disorders [8][9][10][11][12][13][14][15][16]. In recent years, interest in the potential therapeutic properties of CBD in the treatment of cardiovascular [17], cancer [18], metabolic [19], and neurodegenerative [20] diseases has increased.…”
Section: Introductionmentioning
confidence: 99%